\require{AMSmath}

Vergelijkingen oplossen met substitutie

Voorbeeld

Los op:

$(x^2-x+1) (x^2-x+2)= 12$

Neem $u=x^2-x+1$. Je krijgt dan:

$u(u+1)=12$
$u^2+u-12=0$
$(u+4)(u-3)=0$
$u+4=0$ of $u-3=0$
$u=-4$ of $u=3$
$x^2-x+1=-4$ of $x^2-x+1=3$
$x^2-x+5=0$ (geen oplossingen) of $x^2-x-2=0$
$(x-2)(x+1)=0$
$x=2$ of $x=-1$

Opgaven

$
\eqalign{
  & a.\,\,x - 3\sqrt x  =  - 2  \cr
  & b.\,\,\frac{1}
{{(x - 1)^2 }} - \frac{1}
{{x - 1}} - 2 = 0  \cr
  & c.\,\, - (x + 3)^6  + 4(x + 3)^3  =  - 21  \cr
  & d.\,\,3e^{2x}  - e^x  - 2 = 0  \cr
  & e.\,\,sin ^2 x - 4sin x - 5 = 0 \cr}
$


©2004-2017 WisFaq